2013
DOI: 10.1128/cvi.00768-12
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Trivalent Riemerella anatipestifer-Inactivated Vaccine

Abstract: b Riemerella anatipestifer infections cause major economic losses in the duck industry. In this study, a trivalent inactivated vaccine of R. anatipestifer, including strains CH3 (serotype 1), NJ3 (serotype 2), and HXb2 (serotype 10), was developed. Animal experiments showed that the ducks that received two immunizations with the vaccine were 100% protected from challenge with strains from any of the three serotypes (1, 2, or 10). No death or clinical signs of diarrhea, tremors, or limb swelling were shown in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…It had been reported that the RA inactivated vaccine can stimulate vaccinated ducks to produce larger amounts of both Th1 and Th2 cytokines , and a similar phenomenon was observed in the present study. The production of IL‐2, IL‐4, and IL‐10 was higher in the oil‐emulsion vaccine group compared with the control group and the addition of LMS to the inactivated vaccine further promoted secretion of both Th1 and Th2 cytokines.…”
Section: Discussionsupporting
confidence: 90%
“…It had been reported that the RA inactivated vaccine can stimulate vaccinated ducks to produce larger amounts of both Th1 and Th2 cytokines , and a similar phenomenon was observed in the present study. The production of IL‐2, IL‐4, and IL‐10 was higher in the oil‐emulsion vaccine group compared with the control group and the addition of LMS to the inactivated vaccine further promoted secretion of both Th1 and Th2 cytokines.…”
Section: Discussionsupporting
confidence: 90%
“…A trivalent R. anatipestifer inactivated vaccine protecting against serotypes 1, 2 and 10 strains has been developed successfully (Liu et al, 2013). We showed in this study that the inactivated-CH3DM949_1556 vaccine was effective in cross-protecting the ducks from challenge with R. anatipestifer strains WJ4 (serotype 1), Yb2 (serotype 2) and HXb2 (serotype 10) at 100%, 75% and 100% respectively, suggesting that the CH3DM949_1556 strain is an effective vaccine candidate to protect ducks against R. anatipestifer infection in China.…”
Section: Discussionmentioning
confidence: 99%
“…To test the cross-protection, the inactivated CH3DM949_1556 vaccine was prepared and 7-day-old Cherry Valley ducks were immunized as described previously (Liu et al, 2013). Inactivated CH3 vaccine (serotype 1) was used as a control .…”
Section: Evaluation Of Cross-protection Among R Anatipestifer Of Difmentioning
confidence: 99%
See 2 more Smart Citations